Implementasi Model Itqon Dalam Kurikulum Pembelajaran Tahfizhul Quran Di Pondok Pesantren Tahfizhul Quran Ibnu Abbas Klaten - Zubair, Rakhmad; Isnaini, Siti; Nurzaman, Muhammad; Khuriyah, Khuriyah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The rise of Al-Qur'an tahfizh learning programs in various Islamic educational institutions has become a special attraction for some people. On the one hand, it is a symbol, but it also becomes a problem when the tahfizh program offer is only used as a marketing strategy or a competition for the number of memorization achievements. Pondok Pesantren Tahfizhul Quran Ibnu Abbas Klaten is an educational institution that places the syiar of the Koran based on the tahfizh learning curriculum, which balances high quantity and quality. This research is aimed at analyzing the Itqon concepts and models used in the tahfizh learning curriculum. The approach used is qualitative with field research methods. The research was carried out by direct observation and obtained data from interviews as well as documentation which helps provide in-depth information regarding the Itqon model in tahfizh learning. Itqon is one of the memorization methods specially formulated to reinforce Ziyadah activities during tahfizh learning. Supported by Musyafahah Talaqqi Activities from competent mentors. Learning activities are also strengthened by the Murojaah, Juziyyah, and Imtihan programs. The supporting factor is to have a supervisor with a sanad.